Histopathological Association of Adenomyosis with Various Gynaecological Pathologies - Sagar, Nishant; Tomar, Reena; Balhara, Kirti; Mallya, Varuna; Mandal, Shramana; Khurana, Nita (Annals of Pathology and Laboratory Medicine, 2020)
Objective: To study the histopathological pattern of endometrium and associated pathological conditions in patients presenting with abnormal uterine bleeding due to adenomyosis. Material and Methods: The study was conducted at Maulana Azad Medical College, New Delhi and included 87 patients who underwent hysterectomy and were diagnosed with adenomyosis from Jan 2017 to Dec 2019. These cases were subsequently reviewed for presenting symptoms of adenomyosis and correlated with histomorphological features and associated comorbidities. The quantitative variables were expressed as mean and qualitative variables as percentages. Results and Conclusion : The age of the patients who had adenomyosis ranged from 25 to 65 years, majority were in the age group of 40- 50 years. Abnormal uterine bleeding was the most common symptom. The associated histopathological examination reveals pattern of endometrium from proliferative endometrium to endometrial hyperplasia. Estrogen may be a risk factor as it is associated with fibroid and endometrial hyperplasia.